Characteristics of the gut virome in patients with premalignant colorectal adenoma - Pan Zhang; Xiaofeng Tuo; Jiong Jiang; Yue Zhang; Juhui Zhao; Chengzhao Deng; Gang Zhao; Yan Cheng; Lingqin Song; Yan Yang; Ruochun Guo; Huan Zhang; et al. (Journal of Translational Medicine)
Abstract Background The multi-kingdom gut microbiota (e.g., bacteriome, mycobiome, and virome) characteristics of colorectal cancer have been extensively studied, yet there is still an insufficient description of the microbiota features in its early-stage, colorectal adenoma, particularly in the gut virome aspect. Methods Based on the Metagenomic Gut Virus catalogue (MGV) containing 54,118 non-redundant gut viral genomes, this study characterized the virome composition and diversity using publicly available metagenomic sequencing data from 419 individuals with premalignant colorectal adenoma and 552 healthy controls. Furthermore, we identified and assessed the reliability and classification performance of adenoma-associated microbial signatures through comparative analysis and the random forest model. Results Our results revealed a notable shift in the gut virome structure of patients compared to healthy controls, characterized by a significant increase in viral families such as Microviridae, Podoviridae_crAss-like, and Quimbyviridae. At the viral operational taxonomic unit (vOTU) level, we identified 479 vOTU signatures showing significant differences in relative abundances between patients and controls, including some patient-enriched vOTUs tending to infect Bacteroidaceae and Lachnospiraceae. Correlation network analysis revealed specific bacterial species correlated with adenoma-associated viruses, suggesting frequent interactions between them. Moreover, random forest models trained on gut viral and bacterial signatures demonstrated area under the curve (AUC) scores of 0.68, 0.82, and 0.76 for classifying healthy individuals versus patients with tubular adenomas, patients with sessile serrated adenomas, and patients with both conditions, respectively. In three independent validation cohorts, the classification performance achieved AUC scores ranging from 0.61 to 0.65. Conclusions Our study provides insights into the gut virome in premalignant colorectal adenoma, highlighting its potential role in disease development and diagnosis. Further investigations are warranted to elucidate the underlying mechanisms of gut virus-bacteria interactions and validate diagnostic models in larger populations.